SEMIOTIC ANALYSIS OF VERBAL SIGNS FOUND IN FAST FOOD ADVERTISEMENTS - I Putu Ardy Saputra; I Gusti Ayu Mahatma Agung (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2023)
Advertisement is a media platform used by people or companies to promote their product on social media or in public. There are signs in every advertisement. This study is concerned with analyzing the verbal signs found in fast food advertisements. There are two aims of this study: (1) to find out the verbal signs in the fast-food advertisements and (2) to analyze the meaning of the verbal signs that are found in fast-food advertisements. This study uses a descriptive qualitative method, and the data were analyzed based on the theory by Barthes (1967) about the signifier and signified and the meaning. The result of this study shows the verbal sign in the form of written text. In this research, the researchers found twenty-seven verbal signs in fast food advertisements.